The structure of coping among older adults living with HIV/AIDS and depressive symptoms. - Hansen, Nathan B; Harrison, Blair; Fambro, Stacy; Bodnar, Sara; Heckman, Timothy G; Sikkema, Kathleen J (Journal of health psychology, 2013)
One-third of adults living with HIV/AIDS are over the age of 50. This study evaluated the structure of coping among 307 older adults living with HIV/AIDS. Participants completed 61 coping items and measures of anxiety, depression, loneliness, and coping self-efficacy. Exploratory factor analyses retained 40 coping items loading on five specific first order factors (Distancing Avoidance, Social Support Seeking, Self-Destructive Avoidance, Spiritual Coping, and Solution-Focused Coping) and two general second order factors (Active and Avoidant Coping). Factors demonstrated good reliability and validity. Results suggest that general coping factors should be considered with specific factors when measuring coping among older adults.
Keywords: Acquired Immunodeficiency Syndrome; Adaptation, Psychological; Anxiety; Depression; Female; HIV Infections; Humans; Loneliness; Male; Middle Aged; Questionnaires; Self Efficacy